Cobalt and ruthenium complexes with pyrimidine based schiff base: Synthesis, characterization, anticancer activities and electrochemotherapy efficiency - Alkas, Mehmet Esref; Kelestemur, Unzile; Alan, Yusuf; Turan, Nevin; Buldurun, Kenan (Elsevier, 2021)
In this study, a new Schiff base ligand and its two M(II) complexes [CoCl center dot L(H2O)(2)]center dot 2H(2)O, [RuCl(p-cymene)L] were synthesized. The structural features were confirmed from their micro analytical, IR, UV-Vis., (HC)-H-1-C-13 NMR, TGA, X-ray diffraction analysis, mass spectral data and magnetic susceptibility measurements. The Co(II) and Ru(II) complexes displayed an octahedral geometry. In vitro anticancer activities of the Schiff base, Co(II) and Ru(II) complexes were evaluated on the human colon cancer cell line (Caco-2) and biocompatibility characteristics were determined in the L-929 (normal fibroblast cells) cell line by using the MIT assay. Furthermore, we examined the effectiveness of electrochemotherapy (ECT) on cytotoxic activities of these compounds in Caco-2 cancer cell line. According to the findings of the study, Co(II) and Ru(II) complexes showed considerable anticancer properties in the Caco-2 colon cancer cells; however, the ligand did not show significant anticancer activity. It was determined that the combined application of electroporation (EP)+complexes were much more effective than the application of complexes alone in the treatment of Caco-2 colon cancer cells. In a conclusion, the Co(II) and Ru(II) complexes, which showed significant anticancer activity in Caco-2 colon cancer cells, increased cytotoxicity levels by 2.07 and 2.12, respectively in their combined applications with EP. These complexes can be developed as chemotherapeutic agents for colon cancer treatment and can yield promising results when used in ECT. (C) 2020 Elsevier B.V. All rights reserved.
BULDURUN, Kenan/0000-0002-2462-7006; Turan, Nevin/0000-0001-6740-6812
Keywords: Schiff base; Metal complexes; Spectroscopy; Electrochemotherapy; Anticancer activity